Laddningsskena av aluminium för laddning av eldrivna bussar - Baric, Stipe (My University, 2020)
On behalf of AQ Engineering, this work investigates the possibilities and conditions for switching material from copper to aluminum for a charging rail used to charge electric buses. The main purpose of the work is to find a suitable aluminum alloy that can compete with today's copper construction with equivalent performance. In this way, it is hoped to reduce the weight of the rail and reduce the cost. This thesis includes an examination of various aluminum alloys and clad alternatives. Great focus is placed on simulations with the aim of investigating the physical properties and behavior of the aluminum rail under the loads it is exposed to when the bus is charged. The model was built up in SolidWorks and the simulations were carried out in the Electromagnetic simulation (EMS) program. The work presents an appropriate aluminum alloy and surface treatment which, through simulations, shows a similar performance to today's copper alternative.